Grouping of early maturing quality protein maize inbreds based on SNP markers and combining ability under multiple environments - Badu-Apraku, Baffour; Annor, B.; Oyekunle, M.; Akinwale, R.; Fakorede, M.A.B.; Talabi, A.O.; Akaogu, I.C.; Melaku, G.; Fasanmade, Y. (Elsevier, 2015)
Food insecurity and malnutrition are two major challenges facing rural populations in sub-Saharan Africa (SSA). Hybrids of quality protein maize (QPM) have a crucial role here to play because QPM contains increased lysine and tryptophan concentrations and has a higher biological value than the normal maize. Information on the combining ability and heterotic patterns of QPM inbreds is crucial for the success of hybrid programs in the sub-region. Ninety-one diallel crosses derived from 14 early maturing yellow-endosperm QPM inbreds were evaluated from 2010 to 2012 under Striga infested, drought, low-N and optimal environments in Nigeria. The objectives were to (i) examine the combining ability of the set of early yellow QPM inbreds, (ii) classify the inbreds into heterotic groups and identify the best testers (iii) compare the efficiencies of the heterotic grouping methods in classifying the inbreds and (iv) determine the grain yield and stability of the inbreds in hybrid combinations under the research environments. General (GCA) and specific (SCA) combining ability effects were important in the inheritance of grain yield and other traits of the inbreds. However, GCA was more important than SCA under each contrasting environment and across environments suggesting that the additive gene action was more important than the non-additive in the set of inbreds. The SCA effects of grain yield and the heterotic group's SCA and GCA of grain yield (HSGCA) methods classified the inbreds into three groups each, while the heterotic grouping based on GCA of multiple traits (HGCAMT) and the SNP-based genetic distance (GD) methods had two groups each across research environments. There was close correspondence among the classifications of all the grouping methods in terms of placement of inbreds into the same heterotic groups. The SNP-based method was the most efficient and was used to identify TZEQI 87 and TZEQI 91 as the best testers for the SNP-based heterotic groups 1 and 2. The hybrids, TZEQI 87 × TZEQI 93, TZEQI 77 × TZEQI 91 and TZEQI 80 × TZEQI 91 were identified as the most stable and high yielding across research environments and should be commercialized.